Optimalisasi Kesehatan Lansia Dengan Kegiatan Pemeriksaan Kesehatan Diabetes Mellitus Dan Hipertensi - Nurliana M Simbolon; Erliza Erliza; Diana Caroline P; Wirani Nurhasanah; Putri Tri Taruri; Ronalen Br. Situmorang; Emi Pebriani; Meri Epriana Susanti (Jurnal Dehasen Mengabdi, 2026)
Current health trends and issues are starting to shift to non-communicable diseases (PTM), particularly diabetes mellitus and hypertension. The cause of diabetes mellitus and hypertension in elderly is most often the pattern of life habits (life style). The purpose of community service is as an effort to optimize health in the elderly and efforts to prevent further complications. The method is to check blood glucose levels and blood pressure in the elderly and education about diabetes mellitus and hypertension. This community service is carried out in RT.05, Jalan Gedang Subdistrict, Bengkulu City. The results of the activities of 35 people obtained the results that 2.7% of the elderly have diabetes mellitus, 42.8% have hypertension, 20% have diabetes mellitus and hypertension and 31.4% do not have diabetes mellitus and hypertension. Increased knowledge and understanding of the elderly about diabetes mellitus and hypertension is essential to prevent further complications and can be treated promptly. The elderly began to show motivation to routinely follow the activities of the elderly posyandu for the optimization of elderly health.